Changing the Library Brand: A Case Study. Issue 2 (2nd July 2016) - Wynne, Ben; Dixon, Simon; Donohue, Neil; Rowlands, Ian
ABSTRACT: This article outlines some of the opportunities and challenges of changing what the library "brand" means to academic and professional services staff in the rapidly changing environment of UK higher education, taking the University of Leicester as a case study. It makes a practitioner contribution to the growing body of evidence of how libraries are extending their role and how their customers are responding. It begins by considering the drivers for change in the higher education and scholarly information environments and how these are influencing the development of library services at the University of Leicester. The topics considered include researcher development, Digital Humanities, Open Access, independent learning, and curating the university's own information assets. The impact of these developments is outlined and how an evolving approach to strategic marketing is beginning to change perceptions as the boundaries of the library's role extend.